حدیث،علوم ِحدیث اور علوم سیرت میں ادارہ تحقیقات اسلامی کی تصنیفی خدمات: چند اہم کتابوں کا تجزیاتی مطالعہ ............................... Contribution of Islamic Research Institute to the Disciplines of Hadith and Sirah: An Analytical Study - حسین, مبشر (FIKR-O NAZAR فکر ونظر, 2018)
During its lifespan, Islamic Research Institute has published several significant titles respecting various branches of Islamic sciences. The institute has also published some scholarly works on ulum al-hadith and sirah, which are highly appreciated by the scholars. The focus of this study is to introduce the readers to what the institute has published in the discipline of hadith and sirah as well as to evaluate such scholarly works. The following eleven works published by the institute have been selected for the said purpose: 1) Musnad Imam-e Abu Hanifah (in Arabic) 2) Mujam al-safar (in Arabic) 3) Ilm-i Jarh va Tadil (in Urdu) 4) Mujam Istilahat-i Hadith (in Urdu) 5) Ahadith-i Ahkam avr Fuqaha-i Iraq (in Urdu) 6) Khutbat-i Madras (in Urdu) 7) Hujjiyat-i Hadith (in Urdu) 8) Madani Muasharah (in Urdu) 9) Dor-i Jadid main Sirat Nigari ke Rujhanat (in Urdu) 10) The Prophet Muhammad (PBUH): A select bibliography in Western languages (in English), and 11) Hazrat Muhammad ﷺ: Muntakhab Kitabiyat: Urdu Kutub-o Maqalat (in Urdu). Besides, this paper also suggests what steps should be taken next in order to enhance the contribution of the institute to the said disciplines.